Research needs for optimising wastewater-based epidemiology monitoring for public health protection. (12th August 2022) - Robins, Katie; Leonard, Anne F. C.; Farkas, Kata; Graham, David W.; Jones, David L.; Kasprzyk-Hordern, Barbara; Bunce, Joshua T.; Grimsley, Jasmine M. S.; Wade, Matthew J.; Zealand, Andrew M.; McIntyre-Nolan, Shannon
Abstract: Wastewater-based epidemiology (WBE) is an unobtrusive method used to observe patterns in illicit drug use, poliovirus, and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The pandemic and need for surveillance measures have led to the rapid acceleration of WBE research and development globally. With the infrastructure available to monitor SARS-CoV-2 from wastewater in 58 countries globally, there is potential to expand targets and applications for public health protection, such as other viral pathogens, antimicrobial resistance (AMR), pharmaceutical consumption, or exposure to chemical pollutants. Some applications have been explored in academic research but are not used to inform public health decision-making. We reflect on the current knowledge of WBE for these applications and identify barriers and opportunities for expanding beyond SARS-CoV-2. This paper critically reviews the applications of WBE for public health and identifies the important research gaps for WBE to be a useful tool in public health. It considers possible uses for pathogenic viruses, AMR, and chemicals. It summarises the current evidence on the following: (1) the presence of markers in stool and urine; (2) environmental factors influencing persistence of markers in wastewater; (3) methods for sample collection and storage; (4) prospective methods for detection and quantification; (5) reducing uncertainties; and (6) further considerations for public health use. HIGHLIGHTS: Wastewater-based epidemiology (WBE) has been successfully used to track SARS-CoV-2. WBE can monitor populations which are not captured through routine clinical surveillance. WBE has the potential for monitoring many additional indicators of public health. Research is required to validate the use of WBE in public health management. Considerations include integration of WBE with existing public health systems and ethics. Graphical Abstract